Study of the Effect of Tin Addition in Aluminum–Copper Alloys Obtained from Elemental Powders - Pedro José Olendski Elias Junior; Ederson Bitencourt das Neves; Luciano Volcanoglo Biehl; Ismael Cristofer Baierle; Carlos Otávio Damas Martins; Jorge Luis Braz Medeiros (Metals)
Powder metallurgy enables the production of composite materials, which are of great interest to different branches of the automotive, aerospace, and medical industries. This work investigated the sintering of an Al-xCu and Al-xCu-0.1Sn alloy, with copper concentration between 3.5 and 4.5% and tin added in the range of 0.1%. Compressibility curves were drawn, and the samples were sintered in a high-purity nitrogen-controlled atmosphere furnace. The composites were subjected to subsequent solubilization heat treatment, with cooling in low concentration polymer solutions and artificial aging (T6). The samples were studied using optical, scanning electron, Vickers microhardness, and X-ray diffraction techniques. The results indicated the effectiveness of cooling the samples after solubilization in polymer solutions, the influence of the addition of tin on the aging time, and the mechanical properties of the alloys as a function of the T6 cycles applied.